Icaritin Provokes Serum Thrombopoietin and Downregulates Thrombopoietin/MPL of the Bone Marrow in a Mouse Model of Immune Thrombocytopenia - Zhang, Ke; Dai, Zhenfeng; Liu, Runzhe; Tian, Fang; Liu, Xi; Sun, Yi; Zhao, Xin; Pu, Xiaoping (Mediators of Inflammation, 2018)
Immune thrombocytopenia (ITP) is a common acquired autoimmune disease, and thrombopoietin (TPO) is an important cytokine that regulates the production of megakaryocytes and platelets. We have identified a biologically active component, icaritin, from a Chinese herba epimedii extract. Icaritin promotes platelet production and regulates T cell polarization, but its mechanism is not clear. In this study, the BALB/c mouse model of ITP was established by injection of an antiplatelet antibody every other day for seven total times. The antiplatelet sera were derived from guinea pigs immunized with the platelets of BALB/c mice. Mice with ITP were treated with icaritin at low, moderate, or high doses of 4.73, 9.45, and 18.90 mg/kg, respectively, for fourteen consecutive days. The present study shows that icaritin can significantly increase peripheral blood platelet counts and thrombocytocrit, increase the TPO level in serum, attenuate splenomegaly, and reduce the abnormal proliferation of megakaryocytes in the spleen and bone marrow. Icaritin can also downregulate the expression of bone marrow TPO, myeloproliferative leukemia virus oncogene (MPL), and p-Stat3. Our results suggest that icaritin can significantly improve the health of mice with ITP via possible downregulation of p-Stat3 expression in the JAK2/Stat3 phosphorylation signaling pathway and regulation of bone marrow TPO/MPL metabolism.